Characterization of DNA binding and oligomerization domains of stem cell transcription factor Sox9 and Sox5 - Saravanan Vivekanandan (2013)
Sox (SRY-related HMG box) family of proteins is mammalian stem cell transcription factors, playing a pivotal role in regulation of numerous developmental processes. So far nearly 30 Sox proteins have been identified and categorized into eight subgroups of A to G, based on high sequence similarity of the conserved HMG box domain. Unlike other transcription factors, Sox proteins are unique as they recognize and bind the minor groove of DNA, inducing a strong DNA bend of 70-85°, an essential step in eukaryotic transcriptional regulation. Although the HMG domains of all Sox proteins are highly conserved and bind similar DNA elements of sequence (A/T) (A/T) CAA (A/T), they regulate a wide assortment of genes in diverse developmental processes. The functional specificity of Sox transcription factors depends on (i) subtle nucleotide variations in the DNA sequence; (ii) differential minor groove bend as a consequence of HMG domain mediated DNA interaction (iii) different co-factor recruitment through protein-protein interactions.